Primary Anal Cancer Screening Results From 381 Women With Human Immunodeficiency Virus. (5th October 2022) - Liu, Yuxin; Weiss, Kevin; Zamudio, Andrés Ramírez; Hayes, Monica Prasad; Saleh, Mona; Gaisa, Michael M; Sigel, Keith
Abstract: Background: Women with human immunodeficiency virus (WWH) have an elevated risk for human papillomavirus (HPV)-associated anal cancer. Primary anal cancer screening results from this population could inform practice guidelines. Methods: In total, 381 WWH with anal cytology screening, high-risk HPV (hrHPV) testing and genital (cervical or vaginal) cotesting within 6 months were identified during 2012–2019. Those with anal cytology of atypical squamous cells of undetermined significance (ASCUS) or worse underwent high-resolution anoscopy and biopsy. Independent predictors of anal hrHPV, HPV16, and histological anal high-grade squamous intraepithelial lesions (aHSIL) were identified using adjusted logistic regression models. Results: Prevalence of anal hrHPV, HPV16, and ASCUS or worse cytology was 61%, 13%, and 68%. Histological aHSIL was detected in 42% of WWH with ASCUS or worse anal cytology. Prevalence of genital hrHPV, HPV16, and ASCUS or worse cytology was 30%, 4%, and 28%. Genital hrHPV predicted anal hrHPV (odds ratio [OR], 5.05), while genital HPV16 predicted anal HPV16 (OR, 9.52). Genital hrHPV and anal HPV16 predicted histological aHSIL (ORs, 2.78 and 10.9). Conclusions: Anal HPV disease was highly prevalent in this primary screening cohort of WWH. While genital screening results predicted anal disease, rates of isolated anal HPV disease were substantial, supporting universal anal cancer screening for this population. Abstract : Anal HPV disease was highly prevalent in this primary screening cohort of WWH. While genital screening results predicted anal disease, rates of isolated anal HPV disease were substantial, supporting universal anal cancer screening for this population.